2006
DOI: 10.1111/j.1471-4159.2006.03742.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased glutathione biosynthesis by Nrf2 activation in astrocytes prevents p75NTR‐dependent motor neuron apoptosis

Abstract: Astrocytes may modulate the survival of motor neurons in amyotrophic lateral sclerosis (ALS). We have previously shown that fibroblast growth factor-1 (FGF-1) activates astrocytes to increase secretion of nerve growth factor (NGF). NGF in turn induces apoptosis in co-cultured motor neurons expressing the p75 neurotrophin receptor (p75 NTR ) by a mechanism involving nitric oxide (NO) and peroxynitrite formation. We show here that FGF-1 increased the expression of inducible nitric oxide synthase and NO productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
204
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 173 publications
(219 citation statements)
references
References 49 publications
(58 reference statements)
11
204
2
2
Order By: Relevance
“…It has been demonstrated that IFNg induces NO production and increases levels of GFAP in primary astrocytes. 31 Expression of SOD1 G93A or SOD1 G37R in astrocytes is accompanied by increased levels of ROS, including NO, 4,7 and expression of SOD1 G93A in glioblastoma leads to the production of IFNg. 32 How IFNg and ROS cooperate in the acquisition or the consolidation of the reactive status of astrocytes expressing SOD1 mutations remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been demonstrated that IFNg induces NO production and increases levels of GFAP in primary astrocytes. 31 Expression of SOD1 G93A or SOD1 G37R in astrocytes is accompanied by increased levels of ROS, including NO, 4,7 and expression of SOD1 G93A in glioblastoma leads to the production of IFNg. 32 How IFNg and ROS cooperate in the acquisition or the consolidation of the reactive status of astrocytes expressing SOD1 mutations remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,7,8 Among the potential actors of the neurotoxicity of mutant astrocytes, proinflammatory molecules have been proposed. In particular, it has been suggested that prostaglandin D 2 (PGD 2 ) contributes to astrocyte-derived toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parmi les candidats, se trouvent les cellules gliales (astrocytes, microglie, cellules de Schwann) ou les cellules musculaires [16]. Ainsi, le laboratoire de Luis Barbeito a montré que les astrocytes porteurs d'une SOD1m sont capables de provoquer l'apoptose de motoneurones sauvages via un méca-nisme impliquant le stress oxydant et le NGF (nerve growth factor) [17,18]. Ces travaux ont récemment été confirmés par d'autres [19,20] et suggèrent que l'astrocyte pourrait participer à la toxicité envers le motoneurone.…”
Section: Quel Est Le Site De La Toxicité De La Sod1m ?unclassified